2021
DOI: 10.11591/ijeecs.v21.i2.pp987-993
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of PV penetration at different locations in a LV distribution network connected with an off-load tap changing transformer

Abstract: <span>Solar photovoltaic (PV) power generation has shown a worldwide remarkable growth in recent years. In order to achieve the increasing energy demand, a large number of residential PV units are connected to the low voltage (LV) distribution networks. However, high integration of solar PV could cause negative impacts on distribution grids leading to violations of limits and standards. The voltage rise has been recognized as one of the major implications of increased PV integration, which could signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Even at 0% PV penetration, a slight voltage violation is observed at feeder 9 for a peak load of 0.500 MW in this network, as depicted in Figure 10b. A similar study conducted on solar PV penetration at the LV network utilized OpenDSS and found the maximum allowable power capacity [29]. In case 3, the rural network experiences voltage violation that occurs in feeders, 1, 6, and 8 in the no-load simulation scenario when the power capacity exceeds 0.3 MW PV, as shown in Figure 11a.…”
Section: Voltage Violation Potential Of Each Scenario Investigatedmentioning
confidence: 94%
See 1 more Smart Citation
“…Even at 0% PV penetration, a slight voltage violation is observed at feeder 9 for a peak load of 0.500 MW in this network, as depicted in Figure 10b. A similar study conducted on solar PV penetration at the LV network utilized OpenDSS and found the maximum allowable power capacity [29]. In case 3, the rural network experiences voltage violation that occurs in feeders, 1, 6, and 8 in the no-load simulation scenario when the power capacity exceeds 0.3 MW PV, as shown in Figure 11a.…”
Section: Voltage Violation Potential Of Each Scenario Investigatedmentioning
confidence: 94%
“…Even at 0% PV penetration, a slight voltage violation is observed at feeder 9 for a peak load of 0.500 MW in this network, as depicted in Figure 10b. A similar study conducted on solar PV penetration at the LV network utilized OpenDSS and found the maximum allowable power capacity [29]. In the context of voltage violation evaluation, case 3 represents a scenario where a single transformer serves the entire distribution grid.…”
Section: Voltage Violation Potential Of Each Scenario Investigatedmentioning
confidence: 99%
“…The voltage magnitudes at each node were maintained within their acceptable ranges to maintain the stability of the network. Equation (11) defines the voltage constraints.…”
Section: Voltage Constraintmentioning
confidence: 99%
“…The connection of a large number of roof-top PV plants to the low-voltage (LV) network resulted in the violation of voltage limits of certain parts of the network and the violation of thermal limits of some conductors. In addition, reverse power flow was seen in some parts of the networks [10,11]. These violations resulted in limiting the PV-hosting capacity (PVHC) of the distribution networks [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the severity of these impacts depends on several factors, including network topology, geographic location and size of installed PV systems, and weather conditions [10]. The increased active power loss of the network, accompanied by high solar PV integration, is another challenge that could affect the performance of the distribution network [11]. Usually, the network loss represents a U-shape trajectory against the PV penetration level [12].…”
Section: Introductionmentioning
confidence: 99%